2018
DOI: 10.1016/j.drugalcdep.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of economy type on demand and preference for cocaine and saccharin in rats

Abstract: These results show that manipulating economy type can affect cocaine and non-drug reinforcers differently. Opening the saccharin economy decreased saccharin's value. Opening the cocaine economy did not decrease cocaine's value, but instead led to a devaluation of saccharin. These results suggest that cocaine choice may be determined not only by the reinforcers immediately available, but also by those reinforcers' broader contexts of availability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 46 publications
4
20
0
Order By: Relevance
“…Additionally, earlier research indicates that saccharin satiety in rats is controlled by immediate oral sensory stimulation rather than by longer-term post-ingestive consequences such as fullness of the stomach or overhydration (Mook et al, 1981). The short-half life and the lack of post-ingestive consequences for saccharin drinking suggest that the effect of economy type on saccharin reinforcer value observed by Kim et al (2018) was not due to differences in satiation across economies.…”
Section: Economy Type and Saccharin Valuementioning
confidence: 94%
See 3 more Smart Citations
“…Additionally, earlier research indicates that saccharin satiety in rats is controlled by immediate oral sensory stimulation rather than by longer-term post-ingestive consequences such as fullness of the stomach or overhydration (Mook et al, 1981). The short-half life and the lack of post-ingestive consequences for saccharin drinking suggest that the effect of economy type on saccharin reinforcer value observed by Kim et al (2018) was not due to differences in satiation across economies.…”
Section: Economy Type and Saccharin Valuementioning
confidence: 94%
“…For example, individual differences in PR breakpoints or elasticity of demand for drug reinforcers predicts individual differences in drug preference (James et al, 2018;Kearns et al, 2017;Perry et al, 2013;Schwartz et al, 20017). Further, manipulations that decrease PR breakpoints or the essential value of a reinforcer also decrease preference for that reinforcer (Freeman et al, 2014;Kim et al, 2018;Negus, 2005).…”
Section: Reinforcer Valuementioning
confidence: 99%
See 2 more Smart Citations
“…The lack of effect of opening the heroin economy here is the third instance where post-session access to self-administered intravenous drug failed to affect behavior during the session. Previously, we found that post-session access to cocaine (Kim et al 2018) or to heroin (Gunawan et al 2019) did not affect elasticity of demand for these drugs in experiments where, using the same procedures, post-session access to saccharin made demand for saccharin more elastic. These results suggest that, for rats, delayed drug reinforcers do not substitute for current drug reinforcers in the same way that delayed saccharin reinforcers substitute for current saccharin reinforcers.…”
Section: Discussionmentioning
confidence: 65%